2017
DOI: 10.1111/hdi.12626
|View full text |Cite
|
Sign up to set email alerts
|

New diagnosis of bullous pemphigoid after withdrawal of immunosuppressive therapy in a failed renal transplant recipient on hemodialysis

Abstract: The occurrence of the autoimmune blistering disease, bullous pemphigoid (BP), in patients with failed renal allograft is rare and the few reported cases suggest various provocative factors without reaching a consensus. Here we report the case of a patient presenting with bullous lesions soon after the complete discontinuation of immunosuppressant therapy following renal allograft failure. Skin biopsy confirmed the diagnosis of BP. Administration of systemic corticosteroid controlled the occurrence of BP lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…After tapering IS, a significant number of autoantibodies may be generated and contribute to pemphigoid diseases. This is evidenced by nine patients who developed pemphigoid diseases after decreasing or withdrawing of IS ( 35 43 ). Resolution of BP after restarting IS therapy has been observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After tapering IS, a significant number of autoantibodies may be generated and contribute to pemphigoid diseases. This is evidenced by nine patients who developed pemphigoid diseases after decreasing or withdrawing of IS ( 35 43 ). Resolution of BP after restarting IS therapy has been observed.…”
Section: Resultsmentioning
confidence: 99%
“…In the realm of dermatology, the effectiveness of corticosteroids in treating pemphigoid diseases is well-established and corticosteroids remain a mainstay treatment. Studies have shown the effectiveness of corticosteroids in managing BP, even in complex cases like post-transplant recipients or in patients experiencing kidney transplant rejection ( 35 , 41 ). Among 59 reported cases using corticosteroids, 14 (23.73%) patients were recalcitrant ( 23 , 25 , 37 , 44 , 46 , 48 , 50 , 52 , 62 , 67 70 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There have also been reports of BP after renal allograft rejection. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 Here, we present 2 cases of renal allograft rejection associated BP involving oral mucosal lesions. Our literature review suggests that mucosal involvement may be relatively common in BP associated with renal allograft rejection.…”
Section: Introductionmentioning
confidence: 93%